Indoor location technologies for assessing area occupation in preschool environments - Mesquita, Cristina (2017)
In the field of early childhood education, some benchmarks to evaluate the quality of contexts have been developed. One of these benchmarks, developed in the scope of the Effective Early Learning Project, uses the Child Involvement Scale. The Child Involvement Scale uses a list of signals that are recorded on a five-point scale. These signals range from level 1 – 'where a child may seem absent and display no energy, activity is simple, repetitive and passive', to level 5 – 'where a child is concentrated, energetic, and persistent with intense activity revealing the greatest involvement'. The observer records his perception about the concentration, persistence, motivation, energy, satisfaction, complexity and creativity, reaction time and language, trying to establish how the child really feels and experiences the overall learning process. The observations are performed according to a specific format and guidelines, including the definition of specific learning experiences by the teacher. The knowledge gathered from this process results in several aspects, such as in the organization of space, daily routines, and interactions. The importance of an enabling environment is so revealing that educators devote much attention to its organization. Educators define areas of interest in sufficient number so that children have the possibility of choice. They also ensure the visibility and flow of materials between areas in order to expand the learning experiences of children. Materials are arranged in consistent places and the shelves are tagged with child-friendly labels so that children could get out and put away materials themselves. This aims at creating an intentional daily routine that provides a balanced variety of experiences and learning opportunities. Children engaged in both individual and social play, participate in small and large group activities, assisted with clean-up, and developed self-care skills. This set-up and mechanics lead to the possibility to study the impact and interest each area has in the classroom. By constantly measuring the time each child spend in each area, the paths chosen and the number of areas visited by each of them allows the teachers to better understand the interest and success they have among children. The number of children in each classroom makes the measurements of these indicators impossible to do manually. In this paper we assess and present a stat-of-the-art of indoor location technologies able of providing automatic measurements of area occupation in kindergarten classrooms. We focus on technologies that allow dealing with the very dynamic nature of the room environment and that can provide adequate precision and sample time for multiple children simultaneously. We consider several approaches, such as infrared or radio-frequency signals, acoustic location, GPS, trilateration of WiFi devices and mobile phone (GSM) based location. Indoor and noisy environment present a challenging task for assessing, with precision, the location of people, in particular, children in preschool environment that we hope to solve with the combination of several techniques.